Medidas dos tecidos dentogengivais por tomografia computadorizada de feixe cônico em pacientes com erupção passiva alterada - Chiarello, Eduardo Henrique Caldeira-Scherner (2017)
Cone-beam computed tomography (CBCT) in dentistry has been increasingly used, specially when measuring periodontal tissues. The objective of the present study was to analyze, through CBCT, periodontal measurements of the anterior-superior teeth in patients with altered passive eruption (APE), relating the measurements obtained with the involvement of altered active eruption (AAE) and with dental group. In 18 CT scans, linear measurements of the clinical crown, anatomical crown, gingival margin to the cementoenamel junction, and cementoenamel junction to the alveolar bone crest were taken, as well as measurements of soft tissue and bone tissue thickness for each of the 6 anterior-superior teeth . The analyzed teeth were divided into 3 groups: canines (CN) (n = 36), lateral incisors (IL) (n = 36) and central incisors (IC) (n = 36). Data was submitted to statistical analysis (Mann-Whitney test) with a significance level of 5%. The IC group presented a higher percentage of AAE. A lower presence of AAE and a greater intensity of APE in IL were noted. In the IC group, a greater thickness of both soft tissue and bone tissue was observed when compared to the other dental groups. When comparing the presence/absence of AAE, IL and CN showed significant differences in the distance from the gingival margin to the cementoenamel junction. It can be concluded that through CBCT performed on patients with APE, there is no difference in bone biotype regarding the presence/absence of AAE, and that the lateral incisors have proportionally smaller clinical crowns when compared to the other dental groups.